Webgis Application For Searching Nu Mosque In East Java Using The Haversine Method - Rizqi Ibnu Tarmizi; Mas Nurul Hamidah; Arif Arizal (JEECS (Journal of Electrical Engineering and Computer Sciences), 2022)
Indonesia is the country with the largest number of mosques in the world. In East Java, there are many Islamicorganizations, one of which is Nahdhotul Ulama (NU). Nahdhotul Ulama (NU) is one of the socio-religiousorganizations in Indonesia which was founded on 16 Rajab 1344 or to coincide with January 31, 1926 in Surabaya onthe initiative of two leading traditional scholars at that time, K.H Hasyim Asy'ari and K.H Abdul Wahab Hasbullah.Geographic Information System is a computer system that is used to collect, check, integrate, and analyze informationrelated to the earth's surface. Basically, the term geographic information system is a combination of three mainelements, namely system, information, and geography. Thus, an understanding of these three main elements will bevery helpful in understanding GIS. The haversine is an important equation in navigation, giving the great circle thedistance between any two points on the sphere of longitude and latitude. It is a special case of the more commonformula in spherical trigonometry, the law of haversines, relating the sides and angles of a spherical triangle (SphericalTrigonometry).From the calculation results of the haversine algorithm the first trial formula is at the user's location at 1. Jl. RayaSurabaya - Malang, Sawahan, Buduran, Buduran District, Sidoarjo Regency, East Java 61252 found the closest mosquebased on the heversine formula is Darussalam Mosque, jl. Kedemang Singomenggolo no 98 Buduran with a distanceof 1,396 Km. From the calculation results of the haversine algorithm, the first trial formula at the user's location on Jl.Raya Suko No.55, RT.01/RW.01, Ngemplak, Cemeng Kalang, Sidoarjo District, Sidoarjo Regency, East Java 61224found the closest mosque based on the heversine formula is Miftahul Jannah Mosque, jl. Banjar poh village BanjarBendo with a distance of 1,878 Km